Terahertz spectroscopy and solid-state density functional theory calculations of cyanobenzaldehyde isomers - Dash, Jyotirmayee; Ray, Shaurnik; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin B.; Gonnade, Rajesh G.; Ambade, Ashootosh V.; Joshi, Kavita; Pesala, Bala (Journal of Physical Chemistry A, 2015)
Spectral signatures in the terahertz (THz) frequency region are mainly due to bulk vibrations of the molecules. These resonances are highly sensitive to the relative position of atoms in a molecule as well as the crystal packing arrangement. To understand the variation of THz resonances, THz spectra (2-10 THz) of three structural isomers: 2-, 3-, and 4-cyanobenzaldehyde have been studied. THz spectra obtained from Fourier transform infrared (FTIR) spectrometry of these isomers show that the resonances are distinctly different especially below 5 THz. For understanding the intermolecular interactions due to hydrogen bonds, four molecule cluster simulations of each of the isomers have been carried out using the B3LYP density functional with the 6-31G(d,p) basis set in Gaussian09 software and the compliance constants are obtained. However, to understand the exact reason behind the observed resonances, simulation of each isomer considering the full crystal structure is essential. The crystal structure of each isomer has been determined using X-ray diffraction (XRD) analysis for carrying out crystal structure simulations. Density functional theory (DFT) simulations using CRYSTAL14 software, utilizing the hybrid density functional B3LYP, have been carried out to understand the vibrational modes. The bond lengths and bond angles from the optimized structures are compared with the XRD results in terms of root-mean-square-deviation (RMSD) values. Very low RMSD values confirm the overall accuracy of the results. The simulations are able to predict most of the spectral features exhibited by the isomers. The results show that low frequency modes (<3 THz) are mediated through hydrogen bonds and are dominated by intermolecular vibrations.

Tunable nanocarrier morphologies from glycopolypeptide-based amphiphilic biocompatible star copolymers and their carbohydrate specific intracellular delivery - Pati, Debasis; Das, Soumen; Patil, Naganath G.; Parekh, Nimisha; Anjum, Dalaver H.; Dhaware, Vinita; Ambade, Ashootosh V.; Sen Gupta, Sayam (Biomacromolecules, 2016)
Nanocarriers with carbohydrates on the surface represent a very interesting class of drug-delivery vehicles because carbohydrates are involved in biomolecular recognition events in vivo. We have synthesized biocompatible miktoarm star copolymers comprising glycopolypeptide and poly(e-caprolactone) chains using ring-opening polymerization and ``click chemistry''. The amphiphilic copolymers were self-assembled in water into morphologies such as nanorods, polymersomes, and micelles with carbohydrates displayed on the surface. We demonstrate that the formation of nanostructure could be tuned by chain length of the blocks and was not affected by the type of sugar residue. These nanostructures were characterized in detail using a variety of techniques such as TEM, AFM, cryogenic electron microscopy, spectrally resolved fluorescence imaging, and dye encapsulation techniques. We show that it is possible to sequester both hydrophobic as well as hydrophilic dyes within the nanostructures. Finally, we show that these noncytotoxic mannosylated rods and polymersomes were selectively and efficiently taken up by MDA-MB-231 breast cancer cells, demonstrating their potential as nanocarriers for drug delivery.

Tuning of terahertz resonances of pyridyl benzamide derivatives by electronegative atom substitution - Dash, Jyotirmayee (Journal of Infrared, Millimeter, and Terahertz Waves, 2018)
N-(pyridin-2-yl) benzamide (Ph2AP)-based organic molecules with prominent terahertz (THz) signatures (less than 5 THz) have been synthesized. The THz resonances are tuned by substituting the most electronegative atom, fluorine, at ortho (2F-Ph2AP), meta (3F-Ph2AP), and para (4F-Ph2AP) positions in a Ph2AP molecule. Substitution of fluorine helps in varying the charge distribution of the atoms forming hydrogen bond and hence strength of the hydrogen bond is varied which helps in tuning the THz resonances. The tuning of lower THz resonances of 2F-Ph2AP, 3F-Ph2AP, and 4F-Ph2AP has been explained in terms of compliance constant (relaxed force constant). Four-molecule cluster simulations have been carried out using Gaussian09 software to calculate the compliance constant of the hydrogen bonds. Crystal structure simulations of the above molecules using CRYSTAL14 software have been carried out to understand the origin of THz resonances. It has been observed that THz resonances are shifted to higher frequencies with stronger hydrogen bonds. The study shows that 3F-Ph2AP and 4F-Ph2AP have higher hydrogen bond strength and hence the THz resonances originating due to stretching of intermolecular hydrogen bonds have been shifted to higher frequencies compared to 2F-Ph2AP. The methodology presented here will help in designing novel organic molecules by substituting various electronegative atoms in order to achieve prominent THz resonances.
Keywords: Compliance constant; Density functional theory; Ph2AP molecule; Terahertz spectroscopy